Gastric Histopathology of White Rats After Administration of Kedondong Leaves Extract - Sudira, I Wayan; Merdana, I Made; Budiasa, Ketut (Advances in Tropical Biodiversity and Environmental Sciences; Vol 2 No 1 (2018): ATBESDO - 10.24843/ATBES.2018.v02.i01.p05, 2019)
This study aims to determine the effect of ethanol extract of Kedondong leaves (Spondias dulcis G. Forst) on the gastropathological histology of white rats (Mus musculus). A total of 25 healthy male white rats with weights 200-250 g were randomly divided into five groups. A control group was only given a placebo. The treatment group of kedondong leaf ethanol extract sequentially with a dose of 125, 250, 500 and 1,000 mg/kg/day for 21 days orally. On the 22nd day all of the animals were sacrificed for its the gastric, followed by processing for histopathological preparations with Hematoxylin Eosin (HE) staining. The results of the study in all treatment groups were found gastric histology changes in the form of mild inflammatory cell infiltration, mild fatty degeneration and mild necrosis. The number of mice that experienced histopathological changes differed in each group. It can be concluded that the oral administration of kedondong leaf ethanol extract with a range at a dose of 125-1000 mg/kg/d for 21 days does not cause significant histopathological structure disturbance in the stomach of male white rats.